Peran Branding dan Tagline Lead dalam Membangun Budaya Organisasi Perpustakaan Universitas Kristen Krida Wacana - Sinaga, Steven Yehezkiel; Laksmi, Laksmi (Paradigma: Jurnal Kajian Budaya, 2021)
The aim of this research was to examine how the UKRIDA’s motto “Loving, Enlightening, Advanced, Determined” (abbreviated to “LEAD”) builds an organizational culture in the university’s library unit. This research used the qualitative method of ethnography and was conducted by means of observation, interviews and document analysis. The purposive sampling method was used to select the respondents, namely employees who worked in the library unit, were active in research, and had participated in the dissemination of UKRIDA’s “LEAD” values. Data collection was carried out from February to April 2020. The study concludes that the dissemination of LEAD values did not seem to have much influence on the organizational culture at UKRIDA Library, even though there have been several attempts to implement some aspects of the motto. Therefore, this study proposes that the UKRIDA Library should increase its employees’ awareness of its motto on a regular basis. They should also perform a regular evaluation of its employees’ awareness and implementation of LEAD values at UKRIDA Library.